Dunia Fauna Kumpulan Puisi Jantung Lebah Ratu - Satyavadini, Chresna (Humanis; Vol 25 No 3 (2021), 2021)
This article discusses the world of fauna from a collection of poems called Jantung Lebah Ratu by Nirwan Dewanto. This poetry collection contains sixty-six poems with three subtitles; Kantung Kesatu: Biru Kidal, Kantung Kedua: Kuning Silam and Kantung Ketiga: Merah Suam. Of the forty-six poems, nine were taken with the theme of fauna. The focus of this research is two things, namely to reveal the structure and to reveal the world of fauna in the poetry collection Jantung Lebah Ratu. The method used to collect data is the literature study method. The description method is used to analyze the data. The analysis technique used in this research is purposive sampling technique. The analysis of the nine poems uses structural theory from Fananie, Atmazaki, Pradopo and Michael Riffaterre's semiotic theory. Based on the results of the analysis, it was found that the nine poems were analyzed in terms of structure (form and content). Then, to reveal the world of fauna, a semiotic theory was used. The sound play of assonance, alliteration, deep rhyme, final rhyme, imagery and figurative language that the poet wants to convey are able to make readers imagine about the world of fauna.